Enhanced Intrusion Detection System for Discovering Malicious Nodes in Mobile Ad hoc Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Differentiating mobile wireless ad hoc networks from wired networks and even from conventional wireless networks presents new problems in terms of security. Many intrusion detection systems, such Watchdog/Pathrater and Routeguard, have been developed. These systems have close ties to routing protocols. Watchdog is the intrusion detection component, while Pathrater and Routeguard handle the reaction. Each node has its own overhearing watchdog system. Each node may overhear its neighbors' harmful behavior and report them. The speed of the network may be severely impacted, though, if the node that is listening in and reporting itself is malicious. In this article, we discuss how we overcame Watchdog's flaws and introduced our ExWatchdog intrusion detection solution. Discovering rogue nodes that potentially split the network by fraudulently reporting other nodes as misbehaving is the major aspect of the proposed system, and the system then continues to secure the network. Results from simulations demonstrate that our method significantly reduces overhead without clearly increasing throughput.